Automatic Term Extraction on Turkish Scientific Texts - Aygun, Irfan; Kaya, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2020)
In order for a text or collection to be understood, it is very important to understand the terms contained in it. In this study, it is aimed to detect terms in a domain-specific (Cyber Security) corpus. A two-layer method is suggested for the determination of the terms used in single words or phrases. Term candidate words are determined by statistical methods in the first layer. In the second layer, the possibility of using these words in phrases with semantic approaches is checked. In the study, Word2Vec approach was used to determine semantic affinity and 3 different datasets were used. The results show that the terms used in singular or binary patterns were successfully determined using the proposed method. © 2020 IEEE.
2020 International Conference on Decision Aid Sciences and Application, DASA 2020 -- 7 November 2020 through 9 November 2020 -- Virtual, Sakheer -- 166557
Keywords: information extraction; term extraction; terminology; text mining; word2vec